Faktor Risiko Osteopenia pada Remaja - Lina Ema Purwanti; Enggar Prasetyo; Saiful Nurhidayat (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2015)
Introduction: Osteopenia is a condition which means the bone mineral density (BMD/Bone Mineral Density) is lower than the normal peak BMD but not low enough to be classified as osteoporosis. Risk factors that can lead to osteopenia are smoking, drinking softdrinks, less activity, dieting, rarely affected sun and drinking alcohol. This study aimed to identify the risk factors of asteopenia on adolesences. Method: The study design used descriptive. The sample used was a high school student Magetan total of 100 respondents were collected by random sampling. Data were collected with questionniare and analyzed with procentage. Result: From the results of a study of 100 respondents was obtained from less activity factors 5 respondents (5%), rarely exposed to sunlight obtained 32 respondents (32%), dieting factor obtained 34 respondents (34%) smoke got 49 respondents (49%), drink alcohol obtained 18 respondents (18%),and drink softdrink obtained 40 respondents (40%) at risk for osteopenia. Discussion: From the results it can be concluded that smoking is the highest risk factor in the incidence of osteopenia among adolescent. Nicotine contained in cigarettes can reduce absobsi calcium in the bones and cause a decrease in bone density. For any subsequent researchers are expected to conduct research about the relationship of smoking with risk factors for adolescent osteopenia .